Penerapan Pembelajaran Kooperatif dalam Meningkatkan Kemampuan Berbicara Bahasa Indonesia di Sekolah Dasar - Azahra Nasya Atin; Ahmad Azka Pramono (BADAN PENERBIT STIEPARI PRESS, 2022)
This study aims to evaluate the effectiveness of implementing cooperative learning methods in improving Indonesian speaking skills in elementary school students. Cooperative learning methods were chosen for their ability to foster dynamic interactions among students, thereby supporting the development of their speaking abilities. This research employed an experimental design with pre-tests and post-tests conducted on two groups of fifth-grade students at an elementary school. The results showed that the group using cooperative learning methods experienced significant improvements in Indonesian speaking skills compared to the group using conventional teaching methods. Additionally, students in the cooperative learning group demonstrated increased motivation and confidence in speaking. These findings indicate that cooperative learning is effective in enhancing Indonesian speaking skills at the elementary school level.